Serum Free Immunoglobulins Light Chains: A Common Feature of Common Variable Immunodeficiency? - Guevara-Hoyer, Kissy; Ochoa-Grullón, Juliana; Fernández-Arquero, Miguel; Cárdenas, Mariacruz; Pérez de Diego, Rebeca; Sánchez-Ramón, Silvia (Frontiers in Immunology, 2020)
Serum free light chain (sFLC) is a recently proposed biomarker for CVID diagnosis. Most CVID patients present low or undetectable sFLC up-to 10-fold lower compared to other primary antibody deficiencies. Given that κ and λ light chains are normally secreted in excess with respect to immunoglobulins, this finding points to an intrinsic defect of B-cell differentiation in CVID. sFLC levels were prospectively evaluated in a cohort of 100 primary-immunodeficiency (PID) patients and in 49 patients with secondary-immunodeficiency to haematological malignancy (SID). CVID patients had significantly lower κ and/or λ values (mean:κ:1.391.7 mg/L and λ:1.972.24mg/L) compared to “other PIDs” (κ:13.975.88 mg/L and λ:12.927.4 mg/L, respectively,p<0.001 both), and SID (κ 20.922.8 mg/L and λ 12.88.7mg/L, respectively,p<0.001 both). The sum of kappa and lambda (sum κ+λ) in CVID patients (7.257.90 mg/L) was significantly lower respect to other PIDs (26.4413.25 mg/L,p<0.0001), and to SID patients (28.25 26.24 mg/L,p=0.0002). ROC-analysis of the sum κ+λ disclosed an area under the curve (AUC) of 0.894 for CVID diagnosis (SD 0.031; 95% CI: 0.83-0.95, p<0.0001), with optimal cut-off of 16.7mg/L, giving the highest combination of sensitivity(92%), specificity(75%) and NPV(98%). The Relative Risk (RR) for patients presenting a sum κ+λ below 16.7 mg/L was 20,35-fold higher (95%,CI:5,630 to 75,93) for CVID than below this threshold. A similar behavior of the sFLC in our CVID cohort with respect to previously published studies was observed. We propose a cut-off of sum κ+λ 16.7 with diagnostic application in CVID patients, and discuss potential specific defects converging in low or undetectable sFLC.